2006
DOI: 10.1149/1.2353782
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Study of Electrodeposited Fe on n-GaAs(001)

Abstract: The microstructure of Fe films electrodeposited onto n-GaAs͑001͒ from FeCl 2 and FeSO 4 -͑NH 4 ͒ 2 SO 4 electrolytes was examined by X-ray and electron diffraction. Symmetrical -2 X-Ray diffraction from films deposited from chloride solutions indicates a dominant ͑001͒ texture with the presence of additional minority orientations. In contrast, deposition from an ammonium sulfate electrolyte yields films that only exhibit ͑001͒ scattering in the -2 geometry. Transmission electron microscopy ͑TEM͒ crosssectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…For epitaxial electrodeposition of Fe on GaAs, most often the substrate is immersed electrically "hot", but the underlying mechanism for an improvement has not been conclusively identified. 9,13,17 For the same electrolyte as used in the present study, we recently showed that the electrically "hot" immersion with a potential applied before and during immersion, gives better epitaxial properties according to the FMR results. 17 The role of the hydrogen evolution proposed in the present study can explain this favorable effect: in the case of "hot" immersion, a strong hydrogen evolution and Fe deposition are initiated immediately, and the As-H adsorption layer cannot form during immersion prior to Fe deposition.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…For epitaxial electrodeposition of Fe on GaAs, most often the substrate is immersed electrically "hot", but the underlying mechanism for an improvement has not been conclusively identified. 9,13,17 For the same electrolyte as used in the present study, we recently showed that the electrically "hot" immersion with a potential applied before and during immersion, gives better epitaxial properties according to the FMR results. 17 The role of the hydrogen evolution proposed in the present study can explain this favorable effect: in the case of "hot" immersion, a strong hydrogen evolution and Fe deposition are initiated immediately, and the As-H adsorption layer cannot form during immersion prior to Fe deposition.…”
Section: Discussionmentioning
confidence: 66%
“…At first glance, this is unexpected, since the opposite, namely lowering |j|, and thereby the growth rate, was suggested as a route for better epitaxy of Fe on GaAs. 9 However, this route has not been experimentally confirmed. In contrast, in experiments in the systems Au/Si 22 and Bi/GaAs, 23 an improved epitaxial growth and crystallinity of contacts is achieved when electrodeposition takes place at or after application of more cathodic E, and thus higher |j|.…”
Section: Discussionmentioning
confidence: 98%
“…Formation of epitaxial Fe contacts to GaAs(001), GaAs (110), and GaAs(111) from a ferrous ammonium sulphate (Fe(NH 4 ) 2 SO 4 ) electrolytic solution by Bao et al 83 , and a comparison between contacts to GaAs(001) using iron chloride (FeCl 2 ) and ferrous ammonium sulphate electrolytes by Svedberg et al 84 , have demonstrated that electrodeposition may also be a useful technique for ferromagnet/semiconductor contact formation. As electrodeposition is a very lowenergy method, the formation of very abrupt interfaces should be possible by this technique 84 56 .…”
Section: Ferromagnet Film Depositionmentioning
confidence: 99%
“…As electrodeposition is a very lowenergy method, the formation of very abrupt interfaces should be possible by this technique 84 56 . One significant advantage of sputter deposition over MBE growth is the ability to easily apply a magnetic field to the structure during film deposition in order to 'set' a further magnetic anisotropy: in MBE the electronbeam surface analysis tools typically employed to study the surface structure during growth are intrinsically incompatible with such a magnetic 'forming' field.…”
Section: Ferromagnet Film Depositionmentioning
confidence: 99%
“…Iron and iron-nickel alloy deposits have attracted increasing attention as components in spintronics with a semiconductor such as gallium-arsenide (GaAs), where the quality, including preferred orientation and lattice mismatch to the semiconductor is important. [178,179] …”
Section: Characteristics Of Depositsmentioning
confidence: 99%